PENERAPAN MODEL INKUIRI TERBIMBING UNTUK MENINGKATKAN KETERAMPILAN MEMBUAT BENDA KONSTRUK SISISWA KELAS IV SD NEGERI 138 PEKANBARU - Shinta, Shinta; Antosa, Zariul; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract               The problem studied in this research is low skill of students in making objects in construction of subjects Culture Art and Skill. The purpose of this research is to improve skill of making objects construction in class IV SDN 138 Pekanbaru with applaying Guided Inquiry. This study uses classroom and performed in 2 cycluses. Based on the skill assessment seen from the intial data, the average was 55,79 students in the class. After the implementation of guided inquiry model of the first cyclus, the average score of students increased to 63,71 and in the second cyclus, the average score of students increased to 81,74. Based on analysis of the data above it can be concluded that application of guided inquiry model can improve skill making object in construction in class IV SDN 138 Pekanbaru. Keywords : Guided Inquiry, objects construction